Ownership Trends in BSE 100-Index Companies from 2000 a 2014: Evidence and Implications (Global Journal of Human-Social Science, 2016)
Ownership and control of corporations under the watchful stewardship and surveillance of their boards have a significant influence in shaping corporate behavior and the equitable management of relationships between and among themselves the society and communities they serve and the governments of the countries they operate in This paper tracks the movements in corporate ownership in India among its top companies indexed in BSE-100 in the first decade of the new millennium and moving forward in to the second The paper is organized as follows section I provides a brief overview of the development of the corporate format of business organizations section II provides literature related to the topic and describes the sample and its categorization for analysis section III methodology and section IV sets out the findings interpretation and conclusions
Keywords: corporate governance; ownership structure; BSE; trend analysis